43rd Fluid Dynamics Conference 2013
DOI: 10.2514/6.2013-2985
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of hypersonic boundary layer waves using 2-D surface roughness

Abstract: Recent research has shown that 2-D roughness of finite height can damp the second mode instability under certain conditions. For instance, it has been shown that the relative location of 2-D roughness element and the synchronization point is important in determining the 2-D roughness effect on modal growth. It was found that if a roughness element is placed downstream of a disturbance's synchronization point, the disturbance is damped. In this paper, an extensive DNS parametric study on the effect of second mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…The roughness height in the current design is 50% of the local boundary-layer thickness, and the width is two times the local boundary-layer thickness. This particular roughness size is chosen because, in the previous study by Fong et al [19], this roughness size has shown effective damping effects on the second mode. On the other hand, based on the fact that the local boundarylayer thickness is constant, the size of each roughness element is the same.…”
Section: Roughness Design For Second-mode Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The roughness height in the current design is 50% of the local boundary-layer thickness, and the width is two times the local boundary-layer thickness. This particular roughness size is chosen because, in the previous study by Fong et al [19], this roughness size has shown effective damping effects on the second mode. On the other hand, based on the fact that the local boundarylayer thickness is constant, the size of each roughness element is the same.…”
Section: Roughness Design For Second-mode Controlmentioning
confidence: 99%
“…Zhong's group argues that 2-D roughness elements can damp 2-D disturbances if the roughness element, with a height less than the local boundary-layer thickness, is downstream of the synchronization point [14]. This finding has motivated a series of parametric studies on roughness effects including roughness locations, heights, and widths by Fong et al [17][18][19]. All results are consistent with the initial finding that 2-D roughness elements can damp 2-D disturbances and have shown the importance of roughness locations and synchronization locations.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a wavy surface with the wavelength equal to twice the boundary layer thickness delayed the transition onset. Duan et al [19] and Fong et al [15,16,17,18] in a series of studies investigated the effect of two-dimensional roughness on the instability of the second mode (or mode S) by direct numerical simulations (DNS). Their numerical results proved that the roughness located at the downstream of the synchronization point is able to stabilize this mode.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] These tools have enabled broad study on hypersonic boundary layer transition, including geometry changes, 10,11,15,16 operating conditions, 10,11,15,17 mass injection, [16][17][18][19] surface temperature perturbations, 16,18 surface roughness, [20][21][22][23][24][25][26][27] and structural deformations. 28,29 Regarding the latter, it was found that deformed surfaces have a strong influence on flow stability.…”
Section: Introductionmentioning
confidence: 99%